2004
DOI: 10.1177/0886109904268874
|View full text |Cite
|
Sign up to set email alerts
|

Crone Songs: Voices of Lesbian Elders on Aging in a Rural Environment

Abstract: This article reports on a qualitative study with 15 lesbian elders that explored their perceptions of aging in Vermont. Three broad themes were identified as having an impact on the aging process of these lesbian women: self-reliance mediated by interdependence, the state as context, and social supports. Implications for social work education and practice are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Contrary to the prevailing stereotypes, older gay male and lesbian adults are not isolated but have various means of available support (Beeler et al 1999; Christian and Keefe 1997; Comerford et al 2004; Galassi 1991; Grossman et al 2000; Grossman et al 2001; Jacobs et al 1999; Orel 2004; Van de Ven et al 1997; Whalen, Bigner, and Barber 2000), including partners, friends, members of their families of origin, and the larger LGB communities (Berger 1984; Brown et al 2001; Gray and Dressel 1985; Whitford 1997). Furthermore, older LGB adults are sexually active and often in primary relationships (Van de Ven et al 1997); those with partners are less lonely and in better health than those living alone (Grossman et al 2000; Grossman et al 2001).…”
Section: Research Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the prevailing stereotypes, older gay male and lesbian adults are not isolated but have various means of available support (Beeler et al 1999; Christian and Keefe 1997; Comerford et al 2004; Galassi 1991; Grossman et al 2000; Grossman et al 2001; Jacobs et al 1999; Orel 2004; Van de Ven et al 1997; Whalen, Bigner, and Barber 2000), including partners, friends, members of their families of origin, and the larger LGB communities (Berger 1984; Brown et al 2001; Gray and Dressel 1985; Whitford 1997). Furthermore, older LGB adults are sexually active and often in primary relationships (Van de Ven et al 1997); those with partners are less lonely and in better health than those living alone (Grossman et al 2000; Grossman et al 2001).…”
Section: Research Domainsmentioning
confidence: 99%
“…Neighbor and community support was crucial for older lesbians who live in rural settings in terms of providing access to health and transportation assistance (Comerford et al 2004; Moore 2002); yet, only 8% of lesbians older than 50 in the study by Beeler et al (1999) were highly involved in gay and lesbian communities. Furthermore, most gay and lesbian communities are relatively age segregated as a result of age-based stereotypes and differences in generational approaches to survival (Fox 2007).…”
Section: Research Domainsmentioning
confidence: 99%
“…Thirdly, intersections of social class, ethnicity and geography are likely to shape decisions, choices and options (Comerford et al, 2004;Calasanti and Kiecolt, 2007;PurdieVaughns and Eibach, 2008;Stone and Ward, 2011;Fisher et al, 2013). In our own research (Cronin and King, 2014), for instance, we demonstrated how the ability to make retirement choices, which included those related to housing, were structured by intersections of gender, sexuality and social class.…”
Section: Concerning Intersectionsmentioning
confidence: 99%
“…27-29 A small body of research suggests that living in rural areas may also have further adverse implications on the health of lesbian and bisexual women in that they experience less social support and lack of community, as well as more health risk behaviors. 30-32 As a result, rurality has been emphasized by the Institute of Medicine as an area in need of further exploration with regard to sexual orientation-related health disparities. 24 Recently, a study examining lesbian women’s weight status and dietary behaviors found higher body mass index (BMI) and diets higher in protein among rural-residing lesbian women than urban-residing lesbian women.…”
Section: Introductionmentioning
confidence: 99%